Direct determination of the diffusion coefficient variation of coal based on Fick's law and model establishment - Yujin QIN; Fenghua AN; Weiwei SU; Hongfu JIA; Xiangjun CHEN (Meitan kexue jishu, 2023)
Gas diffusion ability directly affects gas exploitation, outburst risk, emission and content determination. In order to study the influence of stress, gas pressure and temperature on gas diffusion coefficient in coal, the gas diffusion coefficient in columnar coal sample was measured with stable concentration difference, which avoided the model dependence that caused by deducing diffusion coefficient through desorption curve. The experimental results shown that the diffusion coefficient was approximately negative linear related to the effective stress for both the adsorbed methane and the non-adsorbed helium, but it was less affected than the permeability. The methane diffusion coefficient decreased as a power function with increasing inlet pressure (concentration gradient), and the relationship with temperature satisfied the Arrhenius formula. The diffusion coefficient measured by the steady-state method was compared with those obtained by the classical model and the time-varying model. It was found that the obtained diffusion coefficients were of the same order of magnitude, the sizes can be several times different, and the variation trend of diffusion coefficient was different with increasing gas pressure. Based on the law of diffusion coefficient affected by pressure (concentration) and temperature, a variable diffusion coefficient model was established. The gas desorption for granular coal at constant and variable temperature was predicted utilizing measured diffusion coefficient for columnar coal, and the prediction results were validated by desorption test. It indicated that the model can well reflect the gas diffusion process in the coal matrix under both constant and variable temperature condition.